Effect of using Korsimu on Oxytocin Levels of Breastfeeding Mothers Post Sectio Caesarea - Pariqa Annisa; Mufdlilah; Anjarwati (Oksitosin : Jurnal Ilmiah Kebidanan, 2025)
The World Health Organisation states that only 47% of babies are breastfed within the first 1 hour of birth, and only 48% of babies under 6 months are exclusively breastfed, with a global target of 70%. The Breastfeeding Mother Oxytocin Chair (KORSIMU) is an innovation that aims to increase levels of the hormone oxytocin, which plays a role in breast milk production. However, there are no quantitative studies that specifically discuss the effect of KORSIMU on oxytocin levels in post sectio caesarea (SC) breastfeeding mothers. To analyse the effect of using KORSIMU on increasing oxytocin levels in post-SC breastfeeding mothers at PKU Muhammadiyah Hospital Yogyakarta. Pre-experimental research design with a one group pretest-posttest design approach with total sampling technique, namely the entire population from April to July was sampled, namely 30 respondents. The intervention given in this study was the use of KORSIMU for 20 minutes. Data analysis using the Wilcoxon test. The results showed an increase in oxytocin hormone levels after the KORSIMU intervention, the p-value of 0.001 <0.05, indicating a significant effect of KORSIMU on oxytocin levels of post-SC breastfeeding mothers. The use of KORSIMU is effective in increasing the oxytocin levels of post-SC breastfeeding mothers and can be an innovative strategy to support optimal breastfeeding, especially mothers who have milk production problems.